DOZ047.30: First year risk factors of mortality and morbidity in esophageal atresia with tracheo-esophageal fistula: data from a population-based national register. (24th June 2019) - Sfeir, R; Rousseau, V; Bonnard, A; Gelas, T; Michaud, L; Boubnova, J; Piolat, C; Irtan, S; Fouquet, V; Mandat, A Le; De Napoli, S; Habonimana, E; et al.
Abstract: Objectives and Study: The aim of our study is to assess the risk factor of mortality and morbidity in a large population-based registry in a population of type III/C esophageal atresia (EA). Methods: Under the umbrella of the national plan for rare disease, a population based register was set up in 2008 recording the data of all the live newborns with EA in France. Based on the registry data, survival and morbidity at 1 year were studied. Morbidity was approached by calculating the rate of full oral autonomy and the hospital length of stay during the first year. Multivariate analysis was performed via multinomial logistic regression to evaluate independent predictors of overall survival and morbidity items among all significant category variables identified on univariate analysis. Results: A total of 1008 patients with type III EA were extracted from the national database born from January first 2008 till 31 December 2014. Mean birth weight was 2610 g (2060 to 3075). Right lateral thoracotomy was used in 93% of cases and primary anastomosis was possible in 95% of cases. Associated abnormalities were present in 53% of patients, VACTERL in 19%, and CHARGE syndrome in 3%. Mortality at 3 months was at 5% and at one year at 6% and was correlated to prenatal diagnosis (odd ratio (OR):2.96 (1.08 to 8.08)), low birth weight (OR: 0.52 (0.38 to 0.72)), and heart defect (OR: 6.09 (1.96 to 18.89)). Length of hospitalization was correlated to birth weight (OR: 0.83 (0.61–1.13)), the difficulty of the anastomosis (OR: 1.59 (0.71–3.55)) and associated abnormalities (OR: 1.93(0.65–5.68)), the prenatal diagnosis is correlated only to the rate of full oral autonomy and not with the length of hospitalization. Conclusions: Surgical procedure or difficulties did not seem to affect survival in this group of patients. In addition to the continuous need to improve care of low weight neonates, our results clearly identify that efforts should be focused on the small group of EA with prenatal diagnosis and/or severe cardiac malformation to reduce even more mortality and morbidity in EA patients.